2011
DOI: 10.1002/art.30147
|View full text |Cite|
|
Sign up to set email alerts
|

Octacalcium phosphate crystals induce inflammation in vivo through interleukin‐1 but independent of the NLRP3 inflammasome in mice

Abstract: Objective. To determine the mechanisms involved in inflammatory responses to octacalcium phosphate (OCP) crystals in vivo.Methods. OCP crystal-induced inflammation was monitored using a peritoneal model of inflammation in mice with different deficiencies affecting interleukin-1 (IL-1) secretion (IL-1␣ -/-, IL-1␤ -/-, ASC -/-, and NLRP3 Conclusion. These data indicate that macrophages, rather than mast cells, are important for initiating and driving OCP crystal-induced inflammation. Additionally, OCP cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 53 publications
0
28
0
4
Order By: Relevance
“…We have also observed in neutrophil-predominant inflammatory responses induced by i.p. OCP crystals injection that neutrophil recruitment was IL-1-dependent but mainly NLRP3 inflammasome independent (38). We hypothesize that NLRP3 inflammasome activation may play a dominant role in a macrophage-dependent inflammation model but a limited role in neutrophilic inflammation.…”
Section: Discussionmentioning
confidence: 78%
“…We have also observed in neutrophil-predominant inflammatory responses induced by i.p. OCP crystals injection that neutrophil recruitment was IL-1-dependent but mainly NLRP3 inflammasome independent (38). We hypothesize that NLRP3 inflammasome activation may play a dominant role in a macrophage-dependent inflammation model but a limited role in neutrophilic inflammation.…”
Section: Discussionmentioning
confidence: 78%
“…It has previously been shown that serum levels of S100A8/S100A9 are increased in a BCP crystal-induced peritonitis model [19]. Studies from our laboratory have also demonstrated that these particulates can directly induce the up-regulation of S100A8 in primary murine macrophages [12].…”
Section: 5mentioning
confidence: 73%
“…While this manuscript was in preparation, a recent study was published which showed the involvement of the NLRP3 inflammasome in basic calcium phosphate crystal-induced IL-1β secretion in vitro (34). However, an in vivo study by the same group did not reveal an effect of the inflammasome on octacalcium phosphate crystal-induced murine peritonitis (35). Using primary macrophages and experimental models of arthritis, both our in vitro and in vivo data presented here clearly identify the NLRP3 inflammasome as an essential player that mediates the pathological response to HA crystals by activating caspase-1 and resulting in the secretion of IL-1β and IL-18.…”
Section: Discussionmentioning
confidence: 96%